Ancient History: What for? The Possibilities between Teaching and Entertainment through Digital Games - Carvalho Rossi, Andrea Lúcia Dorini de Oliveira [UNESP]; Bondioli, Nelson de Paiva [UNESP] (My University, 2021)
There are several visions and proposals concerning the ways – and the content – to approach teaching History in schools, although it is possible to assert that there is one important consensus among the specialists: Teaching History is much more than simply teach ‘dates’ and ‘events’ expecting students to memorize them, but rather it is about working towards the development of the critical-analytical tools of the students, as well as other different transferable skills and abilities, useful in different situations of quotidian life. Based on this understanding, it is possible to see how History and its processes of learning open themselves to a myriad of possibilities and tools, especially those made available by the advances and the development of digital technologies, increasingly ubiquitous. In this sense, the present article aims at, specifically, discussing the possibilities of teaching Ancient History through digital games. Bearing that in mind, two discussions are presented concerning, first, the theoretical discussions on historical literacy – and the concepts of historicity, temporality and historical conscience – and second, the role of the entertainment industry in relation to these discussions. Concerning this last element, it will be sought to present a commentary on the articulation of the possibilities of working towards a historical education, starting from an analysis of textual and graphical narratives of games, such as Assassin's Creed Origins, developed by Ubisoft.
¿Historia antigua para qué? Posibilidades entre la enseñanza y el entretenimiento a través de juegos digitales
História Antiga para quê? Possibilidades entre Ensino e Entretenimento por meio de jogos digitais
Keywords: ancient history; basic education; entertainment; gamification; historical literacy; historicity; history teaching